Effect of Different Levels of Supplementation with Leucaena leucocephala on Weight Gains of the West African Dwarf Goat - E. Tedonkeng Pamo; F. Tendonkeng; J. R. Kana; P. K. Loyem; E. Tchapga; F. K. Fotie (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2004)
The nutritional value and the effect of three levels of supplementation with Leucaena leucocephala on the weight gains and digestibility efficiency of total crude proteins (TCP) were assessed in West African Dwarf goats at the University of Dschang in West Cameroon. Twenty-four goats, about two years of age and with a mean weight of 9.9 ± 2.1 kg, were divided into four groups of six animals. The goats in the supplemented groups received 390 g (group 2), 780 g (group 3) and 1170 g (group 4) of fresh leaves of L. leucocephala corresponding to 7.1, 14.2 and 21.3 g TCP per animal per day, respectively, whereas those of the control group (group 1) did not receive any supplement. Animals were weighed every other week to assess weight gains. L. leucocephala, and Trypsacum laxum samples were fed to the animals in the metabolic cage and feces from the same animals were used to determine TCP digestibility efficiency. Results showed that L. leucocephala had high nutrient contents. The average weights of goats in groups 2 and 3 were statistically similar (P > 0.05) and significantly higher (P < 0.05) than those of goats in groups 1 and 4. The mean daily weight gains of goats in groups 1, 2, 3 and 4 were 18, 46.7, 48.6 and 10.5 g, respectively. The apparent digestibility coefficient of the dry matter was 68.8 ± 2.2, 70.7 ± 1.6 and 72.2 ± 1.1%, and that of TCP was 79.2 ± 1.3, 72.7 ± 2.4 and 72.1 ± 3.1% for the animals that received 390, 780 and 1170 g per day of fresh leaves of L. leucocephala, respectively. Finally, 390 g of fresh leaves (i.e. 157.6 g of dry matter) of L. leucocephala seemed to be the optimum quantity to include in the diet of West African Dwarf goats without the risk of side effects.